2011
DOI: 10.1111/j.1365-3083.2011.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

What Formyl Peptide Receptors, if Any, Are Triggered by Compound 43 and Lipoxin A4?

Abstract: In this study, we determined receptor preferences for compound 43, a nitrosylated pyrazolone derivative, and the eicosanoid lipoxin A4 (LXA4), potent anti‐inflammatory mediators in many experimental in vivo models. Their effects have been suggested to be mediated through binding to formyl peptide receptor (FPR)2 [earlier known as formyl peptide receptor‐like 1 or the lipoxin A4 receptor (ALXR)], one of the two members of the FPR family expressed in neutrophils. Compound 43 activates all neutrophil functions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 36 publications
5
38
0
Order By: Relevance
“…Note particularly that the neutrophil response to compound 43, earlier described as a high-affinity agonist for both human FPR2 and its murine ortholog (14,29), is PBP10 insensitive. This, however, is in agreement with our recently published results showing that compound 43 is primarily an FPR1 agonist (40). High-affinity formyl peptides for FPR1 have been found in both Escherichia coli (fMLF) and S. aureus (fMIFL), and neither of these peptides interacts with FPR2 (41,42); accordingly, we found the neutrophil response to these agonists to be insensitive to PBP10.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Note particularly that the neutrophil response to compound 43, earlier described as a high-affinity agonist for both human FPR2 and its murine ortholog (14,29), is PBP10 insensitive. This, however, is in agreement with our recently published results showing that compound 43 is primarily an FPR1 agonist (40). High-affinity formyl peptides for FPR1 have been found in both Escherichia coli (fMLF) and S. aureus (fMIFL), and neither of these peptides interacts with FPR2 (41,42); accordingly, we found the neutrophil response to these agonists to be insensitive to PBP10.…”
Section: Discussionsupporting
confidence: 80%
“…Apparently, the presence of a formyl group does not play a significant role in mediating receptor specificity between FPR1 and FPR2 (43). We have not determined the effects of the lipid agonist lipoxin A 4 suggested to use FPR2 (9), simply because we have not been able to confirm the receptor preference (40,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Cpd43 was developed as a ligand for FPR2, and has been shown to inhibit neutrophil chemotaxis and markedly reduce mouse ear inflammation (Burli et al, 2006;Sogawa et al, 2011). Alterations in the structure of FPR2 prevent the action of Cpd43, suggesting the presence of specific sites on FPR2 with which Cpd43 interacts (Bena et al, 2012), although this has not been demonstrated physically, for example, using crystallography.Notably, in human neutrophils, Cpd43 has been reported to interact with both FPR1 and FPR2 (Forsman et al, 2011), suggesting that, in at least some conditions, it is a FPR1/2 dual agonist.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Cpd43 exerts anti-inflammatory effects in murine ear inflammation and air-pouch models, which require FPR2 (Burli et al, 2006;Dufton et al, 2010;Sogawa et al, 2011). Mutation studies have identified specific domains in FPR2, which are required for the action of Cpd43 (Bena et al, 2012), but in human neutrophils, Cpd43 has also been reported to interact with FPR1 (Forsman et al, 2011). Its effects have not been studied in the context of arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three receptors, FPR1 and FPR2/ALX display high similarity (69%) in primary sequences. They also share several agonists, including the synthetic hexapeptide WKYMVm (Trp-Lys-Tyr-Met-Val-D-Met-NH2) and non-peptide molecules such as compound 43 (Le et al, 1999;Forsman et al, 2011). N-formylated peptides derived from bacteria or mitochondria are most potent chemoattractants for FPR1, triggering such phagocytic activities as chemotaxis, calcium mobilization, degranulation, and release of superoxide anions (Le et al, 2002).…”
Section: Introductionmentioning
confidence: 99%